Archival studies in Greece and the emerging field of integrated information. Issue 6 (26th August 2014) - A. Giannakopoulos, Georgios; Koumantakis, Ioannis
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to present a survey carried out on a sample of Greek university students (including students of library and archival science) that aimed to map and clarify perceptions of the archive among the students as well as their understanding of the nature of archival science. Moreover, it intends to investigate the information regarding student's opinions and expectations about their archival studies. Design/methodology/approach – Two separate groups took part in this research and were asked to answer a questionnaire with 16 closed-type multiple-choice questions. The first group included 244 individuals, all of them Higher-Educational Institutions students from almost all academic fields. The second group contained 130 students from the three Information Departments of Greece. Findings – The conclusions verify Greek society's view of archives. Even though no consistent definition of the archive seems to exist among the sample of students on which this survey drew, there is a clear understanding of the archive as a source of information emerging from the questionnaires as a shared undisputed fact. Practical implications – The research indicates that archival science is an important part of the information studies. The survey results were taken into account during the revamping of the curriculum of the Department of Library Science and Information Systems, Technological Educational Institute (TEI) of Athens. Originality/value – The study has advanced the understanding of archival science as an informational discipline which has to contribute a great part in the integrated field of information.